Tardive and spontaneous dyskinesia incidence in the general population - Merrill, Ray M.; Lyon, Joseph L.; Matiaco, Paul M. (BMC Psychiatry, 2013)
To identify the incidence rate of spontaneous dyskinesia (SD) and tardive dyskinesia (TD) in a general population and to examine the association between dykinesia and potential risk factors (exposure to metoclopramide [MCP], antipsychotic drugs, and history of diabetes and psychoses).